1986
DOI: 10.1161/01.cir.74.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recording of action potentials from endocardium and epicardium during ischemia in the isolated cat ventricle: relation of temporal electrophysiologic heterogeneities to arrhythmias.

Abstract: We studied the effects of ischemia on transmembrane action potentials, conduction time, and refractory periods of both endocardial and epicardial muscle cells of coronary-perfused cat left ventricles. Oxygenated Tyrode's solution was perfused through the left anterior descending coronary artery, while the preparation was superfused with Tyrode's solution gassed with 95% N2 and 5% CO2. Transmembrane action potentials recorded simultaneously from endocardial and epicardial cells were normal during coronary perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 30 publications
1
43
1
2
Order By: Relevance
“…14,16,20,21 The focus on the arrhythmogenic role of K ATP channel activation has been during acute ischemia. 4,14,17 During this period, epicardial muscle that eventually forms the EBZ undergoes more severe electrophysiological alterations than endocardial muscle, 22,23 partly related to greater activation of the K ATP channels. 24 During subsequent days, muscle cells in the EBZ undergo changes in ion channels that control repolarization, resting membrane potential, and depolarization and are related to changes in ion channel protein synthesis.…”
Section: Role Of K Atp Channels In Ischemic Arrhythmiasmentioning
confidence: 99%
“…14,16,20,21 The focus on the arrhythmogenic role of K ATP channel activation has been during acute ischemia. 4,14,17 During this period, epicardial muscle that eventually forms the EBZ undergoes more severe electrophysiological alterations than endocardial muscle, 22,23 partly related to greater activation of the K ATP channels. 24 During subsequent days, muscle cells in the EBZ undergo changes in ion channels that control repolarization, resting membrane potential, and depolarization and are related to changes in ion channel protein synthesis.…”
Section: Role Of K Atp Channels In Ischemic Arrhythmiasmentioning
confidence: 99%
“…Other studies have demonstrated that, despite similar changes in resting membrane potential, ischemia induces a greater depression of the action potentials of ventricular Epi vs Endo tissues [6,7]. Additional studies have shown a greater Epi sensitivity to a fall of intracellular ATP-induced I K-ATP activation (in response to anoxia) and suggested that this effect may, at least in part, contribute to the greater deterioration of the ventricular Epi action potential to ischemia [8].…”
Section: Introductionmentioning
confidence: 98%
“…Unless otherwise specified, gradients in conduction velocity and in refractory period ranging from endocardium to epicardium were established in keeping with published literature for normal and ischemic cardiac muscle [20]. The importance of such gradients in generating complex patterns of activation has been emphasized by Fenton [10].…”
Section: Endocardial To Epicardial Gradientsmentioning
confidence: 81%
“…Ischemic muscle physiology is simulated by adjusting the local abnormal conduction velocity between 0 and 100 percent of normal and the local refractory period between 50 and 100 percent of normal. Such changes in these physiologic parameters are characteristic of ischemic cardiac muscle [20,21]. The endocardial map of a typical local diseased region is presented in Figure 2.…”
Section: Local Ischemic Tissue Volumesmentioning
confidence: 99%